Impact of land degradation in Bangladesh : changing scenario in agricultural land use - Karim, Z.; Iqbal, M. Anwar; Rahman, Mustafizur; Bāṃlādeśa Kr̥shi Gabeshaṇā Kāunsila. Soils Division (Dhaka : Soils Division, Bangladesh Agricultural Research Council, 2001)
Based on presentations at a workshop organized by Bāṃlādeśa Kr̥shi Gabeshaṇā Kāunsila on December 27, 1998.
Includes bibliographical references (pages 103-106).
Donated By Akbar Ali Khan
Keywords: Land degradation -- Bangladesh -- Congresses; Land capability for agriculture -- Bangladesh -- Congresses; Agriculture; Soils